Uporaba računalniških inteligentnih sistemov v kardiologiji - Molan Štiglic, Milojka (Informatica Medica Slovenica, 2003)
The role of the physician in developing and using intelligent systems is presented in this paper. A success story resulting in new medical knowledge is briefly described.
Keywords: inteligentni sistemi; kardiologija; medicina